Capital social no Brasil: seu conceito e sua presença no âmbito das Unidades da Federação pela medida de associativismo - Jackson Gomes Abrahao (2012)
In the discussions about factors that influence an economy's economic development, social capital emerges as a factor that can significantly impact in that performance. As a rule, referred to as trust, norms and social networks, the issue has, among his early thinkers, Bourdieu (1980, 1986), Coleman (1988, 1990) and Putnam et al. (1993). Evaluating more closely the question of the social groups (networks), authors Olson (1982) and Putnam et al. (1993) are constant references, however, they focus on different types of interaction of these groups with economic development, negatively and positively, respectively. The research developed here finds that, when there is significance in the relationship between social capital measured by the prospect of social groups (especially in more structural concept) with economic growth at the state level in Brazil, social capital behaves in order to combine the groups identified by Olson (1982) and Putnam et al. (1993) positively affecting the rate of economic growth. For so, it was used databases from the Central Register of Enterprises (source: IBGE) and of the Ministry of Development, Industry and Foreign Trade (MDIC), by selecting respectively the information pertaining to groups activities' section and the number of cooperatives and the empirical methodology used is from Roth (2007).